IMMUNOLOGICAL CHARACTERIZATION OF THE PATIENTS WITH CHRONIC UVEITIS CAUSED BY HERPES AND CYTOMEGALOVIRUS - M. D. Guliamova; A. P. Rizopulu; H. M. Kamilov; U. S. Faisieva; A. A. Umarova; F. Yu. Garib; T. U. Aripova (Медицинская иммунология)
Abstract. The study included patients with chronic uveitis caused by herpes simplex virus (HSV), or mixed HSV/ cytomegalovirus (CMV) infections. Deficiencies in CD3+ and CD4+ T lymphocytes and significant increase of CD8+ lymphocyte subpopulations were found in posterior uveitis. A single-pathogen (HSV) infection was characterized by decreased expression of CD3+ and CD4+ lymphocytes, IgG hypoglobulinaemia. Irrespectively of etiology, both groups of the patients exhibited sharp increase in CD16+ cells, as well as suppressed CD25+ receptors for IL-2, increased numbers of activated CD38+ lymphocytes, enhanced expression of late activation markers (CD95+ and HLA-DR+) in both mixed and single-pathogen uveitis. IFN-alpha is detected at low concentrations, or is absent; increased TNF-alpha production was noted in the tears in cases of posterior uveitis.Statistically significant interrelations have been found between expression of HLA-DR+, and CD3+; CD95+ and HLA-DR+; CD95+ lymphocytes and TNFalpha levels in the course of chronic persistence of Herpesviridae in the patients with chronic uveitis. The degree of immunological disturbances correlated with severity of clinical features.